Acessibilidade no corredor expresso: uma avaliação da política pública adotada no Sistema BRT da Avenida Bezerra de Menezes no município de Fortaleza - Lopes, Rosângela de Almeida (2022)
The Bus Rapid Transit (BRT) of the express corridor of Bezerra de Menezes Avenue, implemented in 2015, had accessibility and equity in displacements as its premises. In order to evaluate the public policy of urban mobility contemplated by Law No. 12,587 of January 3, 2012, from the perspective of the development and guarantee of accessibility on this avenue, this work describes the scenario and trajectory of interventions carried out along the road, as well as the disorders, difficulties and improvements to users of public transport, verified after actions carried out by the city of Fortaleza, in the management of former mayor Roberto Claudio Bezerra, between 2015 and 2020. Before deepening the analysis and questioning about the platforms of embarkation and disembarkation - stations of access to buses along the route of the road - there is a theoretical discussion about urbanization, socio-spatial segregation, accessibility, urban mobility, and public transport, founding categories that represent the basis for understanding and discussing the effectiveness or not of accessibility in the express corridor. As a theoretical-methodological proposal, the research is based on the postconstructivist paradigm of Raul Lejano (2012), which seeks a fusion of the text of politics with the context of reality where the policy is effective, and on the in-depth evaluation of Lea Rodrigues (2008), who proposes a more in-depth evaluation of public policies, looking at the relevance that offers the context for understanding the formulation of public policies. Data collection permeates the bibliographic and documentary survey, and is materialized with on-site observation, questionnaires and semi-structured interviews, which were submitted to content analysis, as a data analysis procedure